Pengembangan Video Pembelajaran Bahri (Berkalimah Tayibah Sehari-hari) Berbasis Renderforest tentang Kalimat Tayibah di Sekolah Dasar - Aeni, Ani Nur; Dewi, Cherli Kusumah; Utami, Lisdiana (AS-SABIQUN, 2024)
Learning in the modern era comes with a lot of progress, many skills that must be possessed by students so as to make teachers more innovative in creating a learning climate, one of which is by utilizing technology in learning. However, the fact shows that most teachers, especially in learning PAI subjects in elementary schools, are still very minimal in involving technology as a learning medium for example learning videos, even though as a teacher should have knowledge and skills about the use of technology to create innovative and fun learning. Therefore, the research and development of Renderforest-based learning videos is expected to be able to help teachers in delivering kalimah tayibah material to grade 3 elementary school students more interestingly and fun so that students can easily understand the material and then students practice it in everyday life. The method used by the researcher is the ADDIE model D&D method which is combined with a Students and teachers can access these learning videos on the YouTube app anytime and anywhere. The use of learning videos in the learning process can increase student motivation and create a fun learning experience.students. The research instruments used are interviews and assessment instruments which are then analyzed through the stages of data collection, data reduction, and data verification. BAHRI (Calimah Tayibah Everyday) learning videos in their use have been able to help teachers in a more interesting teaching process and trigger teachers to continue to innovate by utilizing technology in learning. Students and teachers can access these learning videos on the YouTube app anytime and anywhere. The use of learning videos in the learning process can increase student motivation and create a fun learning experience.